Comparative study of the photocatalytic activity of g-C3N4/MN4 (M = Mn, Fe, Co) for water splitting reaction A theoretical study - V N, Dhilshada (Journal of computational chemistry, 2024)
© 2024 Wiley Periodicals LLC.